2014
DOI: 10.1097/md.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Morphological Features of Human Lumbar Discs

Abstract: Recent biomechanics studies have revealed distinct kinematic behavior of different lumbar segments. The mechanisms behind these segment-specific biomechanical features are unknown. This study investigated the in vivo geometric characteristics of human lumbar intervertebral discs.Magnetic resonance images of the lumbar spine of 41 young Chinese individuals were acquired. Disc geometry in the sagittal plane was measured for each subject, including the dimensions of the discs, nucleus pulposus (NP), and annulus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…A recent study on a cohort similar to ours but of Asian origin has shown that the L5-S1 disc has the greatest segmental lordosis of all the lumbar discs [22]. This finding is in agreement with the usual radiographic morphology of the L5-S1 disc, which appears higher anteriorly than posteriorly rather than parallel in a lateral view of the spine [2324].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study on a cohort similar to ours but of Asian origin has shown that the L5-S1 disc has the greatest segmental lordosis of all the lumbar discs [22]. This finding is in agreement with the usual radiographic morphology of the L5-S1 disc, which appears higher anteriorly than posteriorly rather than parallel in a lateral view of the spine [2324].…”
Section: Discussionsupporting
confidence: 88%
“…Disk height and depth, measured from X-ray and magnetic resonance images, varies from 4 to 6 mm posteriorly and 30 to 34 mm between different levels of the spine (minimum values correspond to L1/2 and L5/S1, respectively) ( Table 2) [50,51]. Dimensions of the IVD are useful for informing the required volume for an AF repair biomaterial, for example, a 5 mm square [29] and [33][34][35][36] were multiplied by 0.0981 to convert from kg/cm 2 to MPa.…”
Section: In Vivo Spine Biomechanicsmentioning
confidence: 99%
“…Recently, Zhong et al 1 measured the in vivo morphology of lumbar intervertebral discs and found that the anterior annulus fibrosus was longer than the posterior annulus fibrosus at all lumbar segments except at L5/S1, where both were similar in length. Edmondston et al 8 evaluated the influence of sagittal plane position on lumbar intervertebral disc height and nucleus displacement as seen on MRI in a small asymptomatic population.…”
Section: Discussionmentioning
confidence: 99%